Hubungan Pengetahuan Dan Sikap Terhadap Kinerja Perawat Dalam Pendokumentasian Asuhan Keperawatan Di Ruangan Paru Dan Neurologi Rsu Mayjen H.A Thalib Sungai Penuh Tahun 2025 - Moza Suzana; Thrisia Monica (Nan Tongga Health And Nursing, 2025)
Along with the development of the times, nurses are required to contribute fully in providing their services as much as possible, to produce satisfactory nursing performance for clients. Performance is a world issue today. This occurs as a consequence of public demands for excellent service or high-quality service that is inseparable from standards because performance is measured based on standards. The purpose of this study is to determine the relationship between knowledge and attitudes toward nurse performance in documenting nursing care. This type of research is quantitative and analytical with a cross-sectional study approach. The population in this study were all nurses in the Pulmonary and Neurology Room of Mayjen H.A Thalib Hospital, Sungai Penuh City in 2025, totaling 34 people. The sampling technique used was the Total Sampling technique with a sample of 34 people. The place of this research was conducted in the Lung Room and Neurology Room of Mayjen H. A Thalib Hospital, Sungai Penuh City, implemented in December 2024-Agust 2025. The results showed that more than half of 21 (61.8%) respondents with good nursing performance, and more than half of 19 (55.9%) respondents with high knowledge with statistical test results (Chi-Square) obtained a p-value of 0.007. More than half of 22 (64.7%) respondents with a positive attitude with statistical test results (Chi-Square) obtained a p-value of 0.032. The researcher's suggestion from the results of the study so that it can be applied in daily nursing practice such as providing good nursing performance in documenting care, so that patients will be satisfied with the services provided by nurses.